Direct PCR-based method for detecting Bursaphelenchus xylophilus, the pine wood nematode in wood tissue of Pinus massoniana - Hu, Y.Q. (2012)
Pine wilt disease (PWD), caused by the pine wood nematode (PWN) Bursaphelenchus xylophilus, leads to serious losses to pine forestry around the world. Pinus massoniana, which is vulnerable to be attacked by the PWN, is the dominant species used in pine forestry in China. The objective of this study is to develop a direct PCR-based method for detecting B. xylophilus in the wood of P. massoniana without a separate nematode extraction step. A simple procedure was first developed for isolating B. xylophilus DNA in 5 mg pine wood tissue samples harbouring PWN for detection by PCR amplification. A B. xylophilus-specific amplicon of 403 bp (DQ855275) was generated by PCR from the infested wood tissue. The entire procedure can be completed within 5 h with one pair of primers. This assay can serve as a rapid, cheap and environmentally friendly method to detect B. xylophilus in samples of P. massoniana.